Lesional resective epilepsy surgery in childhood: Comparison of two decades and long-term seizure outcome from a single center - Günbey, Ceren; Bilginer, Burçak; Karlı Oğuz, Kader; Söylemezoğlu, Figen; Ergün, Eser Lay; Akalan, Nejat; Topçu, Meral; Turanlı, Güzide; Yalnızoğlu, Dilek (Elsevier, 2022)
Objective: Epilepsy surgery has shown efficacy in children. We aimed to assess long-term seizure outcome in children who underwent epilepsy surgery and determine predictive factors for seizure freedom.& nbsp;Methods: This is a retrospective study of 196 children who underwent epilepsy surgery between 1994 and 2015 and had a minimum postoperative follow-up of 5 years.& nbsp;Results: The median age at the time of surgery was 9.5 (0.08-19.8) years; 110 (56.1%) had temporal, 62 (31.6%) had extratemporal resections, and 24 (12.2%) had hemispheric surgery. The duration of postsurgical follow-up was between 5 and 20 years (mean +/- SD: 7 +/- 3.2). Overall, 129 of 196 (65.8%) patients had Engel class I outcome at final visit. Among patients who underwent temporal, extratemporal and hemispheric surgery; 84 of 110 (76.4%), 34 of 62 (54.8%), and 11 of 24 (45.8%) patients had complete seizure freedom, respectively (p: 0.016). Patients with tumors had the best outcome, with 83.1% seizure freedom. The number of preoperative antiseizure medications (OR 3.19, 95% CI 1.07-9.48), the absence of postoperative focal epileptiform discharges (OR 8.98, 95% CI 4.07-19.79) were independent predictors of seizure freedom. Across two decades, the age at surgery was decreased (p: 0.003), overall seizure freedom (61.8% vs 68%) did not differ. In the past decade, a higher proportion of malformations of cortical development was operated (14.7% vs 35.9%, p: 0.007).& nbsp;Significance: Our findings showed favorable long-term seizure outcome in children who underwent epilepsy surgery. The results are encouraging for developing centers with limited resources to establish pediatric epilepsy programs.
Keywords: Children; Epilepsy Surgery; Extratemporal Resections; Hemispheric Surgery; Long-Term Seizure Outcome; Temporal Resections